Discussion about principles of lobour organizing in Soviet Russia in 1920 - L V Borisova (RUDN Journal of Russian History, 2010)
In the article the various points of view on the work organization, stated by heads of the Soviet Russia are analyzed during discussion about militarization and forced labor by spring of 1920.